-3=3(x+6)

Simple and best practice solution for -3=3(x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3=3(x+6) equation:


Simplifying
-3 = 3(x + 6)

Reorder the terms:
-3 = 3(6 + x)
-3 = (6 * 3 + x * 3)
-3 = (18 + 3x)

Solving
-3 = 18 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-3 + -3x = 18 + 3x + -3x

Combine like terms: 3x + -3x = 0
-3 + -3x = 18 + 0
-3 + -3x = 18

Add '3' to each side of the equation.
-3 + 3 + -3x = 18 + 3

Combine like terms: -3 + 3 = 0
0 + -3x = 18 + 3
-3x = 18 + 3

Combine like terms: 18 + 3 = 21
-3x = 21

Divide each side by '-3'.
x = -7

Simplifying
x = -7

See similar equations:

| 149-5x=22x+23 | | 5x+13=-137-10x | | 7-5(x-2)=5-3(x+3) | | 11-9x=29-16x | | -9+2z=9z+12 | | 2(x-1)-3(2-x)+4(1-x)=0 | | -23-4x=9-8x | | -134-7x=8x+16 | | -5(k+5)+5k= | | 5(b-4)+25= | | 0=3(2-3x)-7(x-3) | | 10+2(4y+3)= | | 3x-2(12-x)=4(2x-3)+3(x+1) | | 6-5c=-14 | | 6(1-x)+4=3(2-x)-4 | | 4x+10=90-6 | | 40-2(x+1)=90 | | 4k+6=6k-2 | | 6(2x+1)+7=9x+1 | | 6x+9=-119-10x | | 3(7x-1)+8(3-2x)=1 | | -2*5= | | 5(2x+3)-3(x+1)=5 | | 8(x-2)-2(2x-1)=2x+1 | | -2(5r+3)= | | 5a+30b=25 | | 5(3x-4)=8x+1 | | 6a-4=8 | | 3(10a)= | | 2x-3(2-x)=4 | | 4(x+3)-2=2 | | 3(x+1)+2(2x+7)=3 |

Equations solver categories